Research Article: Isolasi dan Identifikasi Senyawa Terpenoid: Research Article: Isolation and Identification of Terpenoid Compounds - Vriezka Mierza; Antolin Antolin; Audi Ichsani; Nurma Dwi; Sridevi Sridevi; Syfa Dwi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Terpenoids are a group of hydrocarbons that are produced in large quantities by plants and are mainly contained in the sap and cell vacuoles. In plants, terpene compounds and their modifications, terpenoids, are secondary metabolites. Terpenoids make up many of the essential oils produced by plants. The content of essential oils influences the use of spice products, both as seasonings, as fragrances, as well as ingredients for medicine, health, etc. The terpenoid-steroid test was carried out using the Lieberman-Buchard reagent which yielded positive results for terpenoids for all fractions. The results obtained for the n-hexane and ethyl acetate fractions on the addition of lieberman-buchard yielded positive results for steroids as indicated by the formation of a green color in the fractions. The purpose of this research article is to provide information to find out what methods are used in isolation in identifying terpenoid compounds and knowing the types of terpenoid compounds obtained from the results of previous research journals.